Genotype x environment interaction analysis of soybean (Glycine max (L.) Merrill) grain yield across production environments in southern Africa - Mwiinga, B.; Sibiya, J.; Kondwakwenda, A.; Musvosvi, C.; Chigeza, G. (Elsevier, 2020)
Development of high yielding and stable cultivars of various crops across the Southern African Development Community (SADC) member states is in line with the recently enacted SADC’s seed harmonisation act. This study, therefore, focused on evaluating soybean [Glycine max (L.) Merrill] lines developed by the International Institute of Tropical Agriculture (IITA) for yield and stability across SADC test environments using the additive main effects and multiplicative interaction (AMMI) analysis. Twenty-five elite lines (five checks and 20 experimental) were evaluated at six locations across four SADC countries during the 2017/18 season in a 5*5 alpha lattice design, replicated three times at each location. The locations were: IITA-SARA, Lusaka West and Chipata in Zambia; Chitedze in Malawi; Nampula in Mozambique; and Rattray Arnold Research Station in Zimbabwe. The environment, genotype, and genotype x environment interaction (GEI) effects were highly significant (p < 0.001), with contributions to total observed variation of 21.04 %, 31.59 % and 47.36 %, respectively. The first two interaction principal component axes (IPCA1 and IPCA2) explained 44 % and 22 %, respectively of the variation due to GEI. Twelve genotypes (48 %) yielded above the grand mean of 3146.31 kg/ha. Check variety SC SAFARI was the highest yielder across environments followed by experimental lines TGx2014-5GM and TGx2002-23DM. Lines TGx2002-17DM, TGx2001-10DM, TGx2001-18DM, TGx2014-24FM, TGx2001-6FM and TGx2002-3DM were winners in Chitedze, Nampula, IITA-SARAH, Lusaka West, Chipata and Rattray Arnold Research Station, respectively. Since TGx2014-5GM was the most stable among all the genotypes across environments, highest yielder (4143 kg/ha) among the experimental lines and second to the highest yielding check (SC Safari), it is therefore recommended for release for production in the SADC after further evaluation. Lusaka West was the highest yielding environment and exhibited strongest interactive forces whilst Nambula had weakest interactive forces.